La princesa vestida con una bolsa de papel - Munsch, Robert N., 1945-; Martchenko, Michael (Willowdale, Ont. : Annick Press, 1989)
Una princesa debe rescatar al principe Ronaldo del dragon. [A princess has to rescue the prince from a dragon.]
Translation of: Paper bag princess.
AD 740
Accelerated Reader
Keywords: Humorous stories -- Juvenile literature; Cuentos humorosos -- Literatura juvenil